Corporate marginal tax rate, tax loss carryforwards and investment functions: empirical analysis using a large German panel data set - Fred Ramb (Deutsche Bundesbank, 2007)
This study is the first empirical analysis to investigate the relationship between the investment behaviour of firms resident in Germany and the empirically determined marginal tax rates developed by John R. Graham. It is based on the Bundesbank's corporate balance sheet statistics for the period 1971-2002. In an autoregressive distributed lag model, the marginal tax rate is shown to be significant, with an elasticity of between 0.1 and 0.2. An error correction model does not produce any plausible results for the marginal tax rate. Graham's marginal tax rates are a complement to the methods typically used to determine the effective marginal tax rates and effective average tax rates.
Keywords: D21; H25; 330; Corporate marginal tax rate; tax loss carryforward; investment behaviour; Investition; Investitionsfunktion; Unternehmensbesteuerung; Grenzsteuersatz; Steuerbegünstigung; Schätzung; Deutschland